The Influence of Parental Attention and Interest in Learning on Students' Economics Learning Achievement Class X Pematang Siantar 3 Public High School - Yohana Rifka Nainggolan; Anton Luvi Siahaan; Pdt. Paulina HN Sirait (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of parental attention and student interest in learning in economics subjects in class X SMA Negeri 3 Pematang Siantar. The variables in this research are parental achievement and interest in learning as independent variables and learning achievement as the dependent variable. This type of research is quantitative research with an E-xpost Facto approach , with a research population of class X students at SMA Negeri 3 Pematang Siantar and a research sample of class Data collection techniques used instruments: (1) parental attention questionnaire, (2) learning interest questionnaire, and (3) learning achievement questionnaire. The results of this research show that: (1) there is a positive and significant influence of learning facilities on learning outcomes. This result can be seen in the t test where the calculated t value of parental attention (5.299) > t table value (1.65462) which means the variable is significant. (2) there is a positive and significant influence of interest in learning on learning achievement (5.095) > t table value (1.65462) which means this variable is significant. (3) Parental attention and interest in learning together influence learning achievement, this result can be seen in the F test where the calculated F value (17.485) is > compared to the F table value (2.66). The R Square coefficient of determination test was found to be 0.185, meaning that 18.5% of the variables of parental attention and interest in learning had an influence on student learning achievement at SMA Negeri 3 Pematang Siantar and the remaining 81.5% was the influence of other variables not examined in this research.